Desarrollo tecnológico para emprendimiento social (2017)
This work seeks to apply the technological tools available for the creation of a social entrepreneurship model, based on the generation of solutions focused on the coverage of specific energy needs in Colombian communities with limited access to the resource. All this, from the integration of specialized environments in the engineering area, the use of clean energies, the focus on social interests that currently require attention and the methodologies of social innovation. Taking into account the real framework of sustainable development. This, through the design of a calculation model to determine the social, financial and technological viability of different solutions proposed, using solar and hydrokinetic energy for the generation of electricity in communities with limited access to it.